Cytokines in the Microenvironment of Waldenström’s Macroglobulinemia - Elsawa, Sherine F. (2009)
Waldenström’s macroglobulinemia (WM) is a lymphoplasmacytic lymphoma characterized by the overproduction of a monoclonal IgM protein that accumulates in the serum. Although the pathologic findings in this disease entity are reasonably well defined, the mechanisms that regulate malignant B-cell growth and monoclonal protein synthesis are less well understood. Cytokines are known to regulate many biologic processes in normal lymphocyte development including immunoglobulin production, and the presence of cytokines within the tumor microenvironment of WM is likely to contribute to malignant cell growth and survival as well as immunoglobulin production. Several studies have suggested that cytokines are potentially dysregulated in WM, however the precise role played by cytokines in WM biology is not clearly defined. This report therefore highlights our current understanding of the role of cytokines in the microenvironment of WM and how they affect malignant cell persistence and function in the bone marrow of patients.